Riverine Ecosystem Management 2018
DOI: 10.1007/978-3-319-73250-3_4
|View full text |Cite
|
Sign up to set email alerts
|

River Hydrology, Flow Alteration, and Environmental Flow

Abstract: "The water runs the river." This chapter focuses on the river flow as the fundamental process determining the size, shape, structure, and dynamics of riverine ecosystems. We briefly introduce hydrological regimes as key characteristics of river flow. Hydrological regimes are then linked to habitats and biotic communities. The effects of flow regulation as a result of human activities such as water abstraction (irrigation and hydropower), river channelization, land use, and climate change are demonstrated. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 41 publications
0
66
0
1
Order By: Relevance
“…Hence, habitat conditions within channels and accompanying floodplains differ between rivers following the pattern of flow and the nature and availability of material it carries. Consequently, different habitat characteristics such as river bars and riffle-pool sequences of river channels and floodplains are produced and sustained (Zeiringer, Seliger, Greimel, & Schmutz, 2018). It is thus vital that the river flows are capable enough to transfer bed or bank sediment, and they take place recurrently to alter the morphology of the river channel (Wolman & Miller, 1960).…”
Section: The Natural Flow Regime (Nfr)mentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, habitat conditions within channels and accompanying floodplains differ between rivers following the pattern of flow and the nature and availability of material it carries. Consequently, different habitat characteristics such as river bars and riffle-pool sequences of river channels and floodplains are produced and sustained (Zeiringer, Seliger, Greimel, & Schmutz, 2018). It is thus vital that the river flows are capable enough to transfer bed or bank sediment, and they take place recurrently to alter the morphology of the river channel (Wolman & Miller, 1960).…”
Section: The Natural Flow Regime (Nfr)mentioning
confidence: 99%
“…These novel flow regimes and climate changes cause the decline of healthy and resilient communities (Strona & Lafferty, 2016). In an all-inclusive review, Poff and Zimmerman (2010) and Zeiringer et al (2018) F I G U R E 2 Indicators of river health reported that most of the research found undesirable ecological response to change in NFR (Table 1).…”
Section: Impact Of Altering Nfr On the Biotic Composition Of Riversmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the construction of any river channel reservoir, the defining parameter of any hydroecosystem -continuity of river flow -is practically leveled [2]. While flow velocity affects the formation of some important "economic" indicators of the aquatic ecosystem: productivity, biodiversity, quality of water resources [3,4].…”
Section: Introductionmentioning
confidence: 99%